Estudio sobre las implicaciones protocolarias de la bandera del Vaticano - Fuente, Daniel Garcia (Journal of the sociology and theory of religion, 2021)
This study focuses on the protocol uses of the Vatican City State flag. We will delve into existing regulations, traditions and the use of it in different situations. The Vatican is an independent State with a legal base and with official symbols that represent it and give it identity at national and international level. Like any other flag of another country, its emblem is subject to customs and regulations that must be complied with when using it.